Comparison of positive BioFire FilmArray meningitis/encephalitis (ME) panels, CSF cultures, CSF parameters, clinical presentation and in-patient mortality among patients with bacterial and fungal meningitis - Thein Myint; Jaime Soria; Yuanzheng Gao; Marice Ruiz Conejo Castillo; Vaneet Arora; Julie A. Ribes (Microbiology Spectrum)
ABSTRACT The BioFire FilmArray meningitis/encephalitis panel (MEP) was brought to the University of Kentucky in 2016 to aid in the identification of community-acquired meningitis and encephalitis (ME). This panel has shown variable performance with some institutions showing high sensitivity and specificity for many pathogens but others seeing false positives during clinical use. We evaluated the panel’s performance using retrospective chart review of patients at the University of Kentucky from October 2016 to September 2022, including 7,551 MEP results. Cerebrospinal fluid (CSF) samples with positive results for bacterial and fungal pathogens were compared with CSF and blood cultures, other laboratory parameters, and clinical presentations, to classify MEP results as true positive (TP), likely TP, or false positive (FP). Of 132 patients with positive bacterial or fungal MEP results, 48.9% of bacterial and 88.9% of cryptococcal analytes were classified as TP. The positive predictive value (PPV) varied by organism, with the highest being Listeria monocytogenes and Neisseria meningitidis. One-third of the FP results were Streptococcus agalactiae. Among patients with likely TP, 75.7% (28 out of 37) received oral or IV antibiotics before blood or CSF culture. MEP was 100% specific compared to culture. The PPV based on pathogen ranged from 78.6% to 100%. Interestingly, 27.4% (29 out of 106) cases (excluding FPs) would have no pathogen definitively identified if MEP had not been used. This study highlights the utility of MEP in rapidly diagnosing ME, particularly in patients pretreated with antibiotics. It also emphasizes the importance of correlating MEP results with clinical assessments and other diagnostic tests to assure accuracy.IMPORTANCEThis study compares the performance of the meningitis/encephalitis panel (MEP) in detecting bacterial and fungal pathogens with cerebrospinal fluid cultures and other parameters. Almost half of bacterial analytes of MEP had positive cerebrospinal fluid (CSF) or blood cultures; the remaining 42% of bacterial analytes were correlated with clinical presentation and other CSF parameters. 27.4% (29 out of 106) cases would not have had a pathogen definitively identified if the MEP had not been used. This study highlights the importance of using MEP as a diagnostic tool, especially in patients who have already received antibiotics, where traditional culture-based methods may not be diagnostic. This research underscores the use of MEP in improving the speed of diagnosing meningitis. However, it emphasizes that MEP can produce false positive results in some patients. It is therefore necessary to interpret MEP results together with clinical assessments and other diagnostic tests to ensure the most accurate diagnosis.